Carcinoma ex pleomorphic adenoma of the parotid gland: a multi-institutional retrospective analysis in the Northern Japan Head and Neck Cancer Society. (1st November 2016) - Suzuki, Masahiro; Matsuzuka, Takashi; Saijo, Satoshi; Takahara, Miki; Harabuchi, Yasuaki; Okuni, Tsuyoshi; Himi, Tetsuo; Kakizaki, Tomohiko; Fukuda, Satoshi; Yamada, Kazuyuki; Nagahashi, Tatsumi; Abe, Takahisa; et al.
Abstract: Conclusion: The 3-year progression-free survival rate of non-invasive salivary duct carcinoma (SDC) or adenocarcinoma not otherwise specified (NOS) was significantly better than that of invasive SDC or adenocarcinoma NOS in Carcinoma ex pleomorphic adenoma (CXPA). The presence of invasion is an important prognostic factor for SDC and adenocarcinoma NOS in CXPA. Objectives: CXPA is a rare parotid gland malignant tumor for which therapy is not yet standardized. The purpose of this study was to review the characteristics of CXPA patients and to analyze their outcomes in the Northern Japan Head and Neck Cancer Society. Method: The medical records of 33 patients who had been provided initial treatment in 12 institutes of northern Japan from 2002–2011 were reviewed as a multi-institutional retrospective study. Results: The 3-year overall and progression-free survival rate of all patients was 79.9% and 76.8%, respectively. Both the 3-year overall and progression-free survival rates were 87.5% for patients with non-invasive SDC or adenocarcinoma NOS. The 3-year overall and progression-free survival rates for patients with invasive SDC or adenocarcinoma NOS were 60.4% and 30.5%, respectively. The progression-free survival rates for patients with invasive SDC or adenocarcinoma NOS was significantly poor ( p  < 0.05).